Celebrating IWD 2021: Focus on women in gender research and leadership - Grace Bruno Duncan - Duncan, G.B. (International Livestock Research Institute, 2021)
Grace Bruno Duncan, a chicken business entrepreneur in Tanzania explains the COVID-19 crisis has prevented her from accessing her customers, most of whom are hotel businesses. Travel restrictions have reduced the number of customers visiting hotels and as such, most of her sales chicken sales have gone down.